Gabon produces fertilizer from mining project - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Gabonese Republic has recently completed a 12-month project that has demonstrated that fertilizer can be produced cheaply and viably from local raw materials. This low cost project (ECU 642,000) was funded jointly by the European Development...